2019
DOI: 10.1111/ggi.13621
|View full text |Cite
|
Sign up to set email alerts
|

Association of olfactory impairment with indexes of sarcopenia and frailty in community‐dwelling older adults

Abstract: Aim Individuals with olfactory or gustatory impairment often have associated difficulties with food‐related activities. As both functions decline in older adults, we investigated the association of these impairments with sarcopenia/frailty indexes in community‐dwelling older adults. Methods A total of 141 participants (69 men and 72 women, mean age 73.0 years) were enrolled. Odor identification was examined using the Open Essence test. Salty and sweet tastes were assessed using a whole‐mouth gustatory test. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 28 publications
1
56
1
Order By: Relevance
“…9,53,54 One study of 141 older Japanese participants using objective smell and taste tests found a significant association of mOD with a frailty index, but not mGD. 55 Meanwhile, data from a prospective populationbased study of 1035 Italian persons aged ≥65 years revealed an association between self-reported OD and frailty, which varied according to levels of serum interleukin-6 (IL-6), a marker of inflammation. 56,57 In agreement, our analysis of a nationally representative sample of older adults in the United States identified self-reported olfactory and gustatory dysfunction, as well as measured olfactory dysfunction, as being independently associated with measures of frailty.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,53,54 One study of 141 older Japanese participants using objective smell and taste tests found a significant association of mOD with a frailty index, but not mGD. 55 Meanwhile, data from a prospective populationbased study of 1035 Italian persons aged ≥65 years revealed an association between self-reported OD and frailty, which varied according to levels of serum interleukin-6 (IL-6), a marker of inflammation. 56,57 In agreement, our analysis of a nationally representative sample of older adults in the United States identified self-reported olfactory and gustatory dysfunction, as well as measured olfactory dysfunction, as being independently associated with measures of frailty.…”
Section: Discussionmentioning
confidence: 99%
“…Although few studies examine the relationship between chemosensory dysfunction and frailty, findings have been inconsistent 9,53,54 . One study of 141 older Japanese participants using objective smell and taste tests found a significant association of mOD with a frailty index, but not mGD 55 . Meanwhile, data from a prospective population‐based study of 1035 Italian persons aged ≥65 years revealed an association between self‐reported OD and frailty, which varied according to levels of serum interleukin‐6 (IL‐6), a marker of inflammation 56,57 .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was found that idiopathic age-related decline in olfactory function was much smaller in the healthy, nonmedicated, non-smoking population (Mackay-Sim et al, 2006). On the contrary, it was shown that taste and smell disorders were associated with an increased risk of frailty in the older population (Somekawa et al, 2017;Harita et al, 2019). Among the mortality studies, controlling for performance in activities of daily living or frailty score did not attenuate the effect (Pinto et al, 2014;Schubert et al, 2016).…”
Section: Accelerated Brain Agingmentioning
confidence: 99%
“…Olfactory identification was evaluated using a card‐type olfactory test, the Open Essence (OE) test, with 12 odorants (FUJIFILM Wako Pure Chemical, Osaka, Japan) 12 . According to the OE score, participants were divided into normosmia (OE score 12–7), dysosmia (OE score 6–4) and anosmia (OE score ≤3).…”
Section: Methodsmentioning
confidence: 99%